Pengaruh Hypnoteaching Terhadap Hasil Belajar Mahasiswa Keperawatan - Amelia, Sherly; Kartika, Imelda Rahmayunia (Universitas Fort De Kock Bukittinggi, 2020)
Background: Hypnoteaching is the art of communicating in teaching by giving suggestions so that students become smarter. Through the suggestions given, it is hoped that they will be aware and enlightened that there is extraordinary potential which they have never optimized in learning. Method: This reasearch was quasy experimental research. The sample in this study was the nursing student in third semester. The sample technique used total sampling. The sample was divided into two groups, 40 students in Class B for the intervention group and 40 students in Class A for the control group. Data collection techniques used documentation techniques to obtain pretest data, observation to control the method hypnoteaching and tests to obtain data posttest. Work group learning outcomes measured before starting the learning process by using 20 items through exam questions after the pre-test and learning methods hypnoteaching in the intervention group and the conventional Data in this study were tested using Independent test T-Test. Results: The results showed that there was an effect of themethod hypnoteaching on student learning outcomes. This is evidenced by the class average scores with the two post-tests using themethod hypnoteaching of 85.86 and 88.16, while the average class scores using conventional methods are 70.79 and 77.95. With a significance value of 0.000 and 0.004, it means that the significance is <0.05. Conclusion: It can be concluded that the hypnoteaching method can improve learning outcomes and can be used as a learning method.Keywords: Hypnoteaching, Learning Outcomes, Nursing Students